Strengthening Understanding of Sharia Finance and Dissemination of Sharia Bank Products for the Community of Tanjung Rema Darat Martapura - Aisyah, Lisda; Mardini, Yulida; Dairobi (Amala Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service activities are one of the efforts to carry out the Tri dharma of Higher Education, which includes education, research and community service. Therefore the Faculty of Islamic Economics and Business at the Martapura Darussalam Martapura Islamic Institute in 2023 has a community service program organized by lecturers in accordance with the Institute's Vision and Mission. In this program, we carry out community service activities entitled "Strengthening Islamic Financial Understanding and Dissemination of Islamic Bank Products for the people of Tanjung Rema Darat Martapura. The results of the implementation of the increase in financial literacy and inclusion indexes are the result of good cooperation between the OJK, related ministries/institutions, the financial services industry and various other parties, both within the National Financial Inclusive Council and the Team for the Acceleration of Regional Financial Access (TPAKD). increased from 171 in 2019 to 462 TPAKD in 2022.